2007
DOI: 10.1007/s10791-007-9032-x
|View full text |Cite
|
Sign up to set email alerts
|

Bias and the limits of pooling for large collections

Abstract: Modern retrieval test collections are built through a process called pooling in which only a sample of the entire document set is judged for each topic. The idea behind pooling is to find enough relevant documents such that when unjudged documents are assumed to be nonrelevant the resulting judgment set is sufficiently complete and unbiased. Yet a constant-size pool represents an increasingly small percentage of the document set as document sets grow larger, and at some point the assumption of approximately co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 21 publications
(25 reference statements)
4
66
1
Order By: Relevance
“…Test collections are research tools that are most useful when they are reusable, that is, when they fairly evaluate retrieval systems that did not contribute to their construction [1]. Thus, a reusable test collection can be used to evaluate systems even after the original evaluation that created the collection has concluded.…”
Section: Building Pooled Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Test collections are research tools that are most useful when they are reusable, that is, when they fairly evaluate retrieval systems that did not contribute to their construction [1]. Thus, a reusable test collection can be used to evaluate systems even after the original evaluation that created the collection has concluded.…”
Section: Building Pooled Collectionsmentioning
confidence: 99%
“…Diversity is important from at least two perspectives. Previous work has tied the reusability of a collection built using pooling to the diversity of the retrieval runs that form the pools [1]. Diversity in participant submissions also serves as a proxy indicator that researchers are trying different (novel) retrieval techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the bias can be systematic against systems that are different in nature from those which contributed to the pool. For instance, Buckley et al [2007] suggest that recent large TREC collections have their pools flooded with documents rich in query keywords, and are biased against retrieval methods that attempt to go beyond keyword matching. Such systematic bias is not merely unfair to certain systems, but is an obstacle to an entire direction of potential retrieval improvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the topic was later revisited, Buckley et al (2007) identified that the reason for the small bias was because the submissions to the task were too similar; upon repeating the experiment using a novel system as part of the TREC Robust track, they identified a 23% point drop in average precision scores! 8…”
Section: Related Workmentioning
confidence: 99%